6. Serangan Israel terhadap Kapal Bantuan Kemanusiaan Mavi Marmara Tahun 2010 - Antonius Pramudya Adityas; Ika Riswanti Putranti; Fendy Eko Wahyudi (Journal of International Relations Diponegoro, 2017)
Israel and Palestine are two countries involved in protracted and restless conflicts. In 2010,the pro-Palestinian movement named Gaza Freedom Flotilla Organization was going tosend humanitarian aid to Gaza by the sea. Amid the trip, one of the ships in the Gazahumanitarian aid group Freedom Flotilla named Mavi Marmara was attacked by IsraelDefense Forces. The purpose of this study is to explain the reason of Israeli attack on MaviMarmara aid ship. The research question will be analyzed by theory of securitization toexplain the reason of why Israel attacked the humanitarian aid ship Mavi Marmara. Troughthe securitization theory, it will be explained on how a state responses a nonpolitical issueand alters it into a political issue that requires an effective policy. This research usesexplanatory method to understand the reason behind the attack on Mavi Marmara. Thediscussion in this study is based on Israel’s point of view. The result of this research is thatthe attack on the Mavi Marmara aid ship was a defense strategy by the Israeli Governmentin order to tackle the possible threats to dismiss Israeli’s Blockade to Gaza as part of it’sprotection policy.